Role of growth temperature in photovoltaic absorber CuSbSe2 deposition through e-beam evaporation. (15th March 2020) - Goyal, Deepak; Goyal, C.P.; Ikeda, H.; Malar, P.
Abstract: In this study, CuSbSe2 chalcostibite thin films were deposited on glass substrates held at different temperatures using e-beam evaporation from the pre-synthesized CuSbSe2 bulk source material. Bulk CuSbSe2 source compound was synthesized by mechanical ball milling of constituent elements. Substrate temperature and growth condition were optimized to obtain the near stoichiometric chalcostibite thin films. Structural, morphological and optical properties of the synthesized thin films were investigated using x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), dynamic force microscopy (DFM), UV–vis–NIR spectroscopy and Raman spectroscopy. Positive value of the measured hall coefficient indicated the p-type nature of CuSbSe2 thin films having a carrier concentration of 5.6 × 10 15 cm −3 . The thin films were found to have a direct optical band gap (Eg ) value of 1.2 eV and absorption coefficient greater than 10 4 cm −1 .